The BIOLOGICAL EFFICACY OF MIXED LIGAND COPPER(II) COMPLEXES OF N(4)-SUBSTITUTED THIOSEMICARBAZONE AND DIIMINE CO-LIGANDS AS CHELATING N, N’- DONOR LIGAND - NEELAVENI RAJENDRAN; NITHYA KAMATCHI; VASANTHA SOLOMON (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In modern years, the biggest dare is to develop new chemotherapeutic agents with high efficiency as well as low toxicity. Hence, to defeat this challenge, extensive endeavors were taken on thiosemicarbazone based metal complexes. Methods: A sequence of nine thiosemicarbazone based diimine copper(II) complexes derived from three sulfur-containing ligands N-methyl-2- ((1-methyl-1H-pyrrol-2-yl)methylene)hydrazinecarbothioamide H(L1), N-ethyl-2-((1-methyl-1H-pyrrol-2-yl)methylene)hydrazinecarbothioamide H(L2), and N-benzyl-2-((1-methyl-1H-pyrrol-2-yl)methylene)hydrazinecarbothioamide H(L3). The molecular structures and coordination possibilities of thiosemicarbazone ligands toward the central metal ions have been validated by analytical and spectral techniques such as molar conductance, elemental analysis, ultraviolet–Vis, Fourier-transform infrared, and electron paramagnetic resonance spectroscopy confirms that the thiosemicarbazones ligands are coordinated to copper through NS’ donor and NN’ donor of diimine. The antimicrobial activity and DNA cleavage effectiveness of thiosemicarbazone derivatives and copper(II) complexes were assessed by disc diffusion and agarose gel electrophoresis methods. Results: All the spectral studies authenticated that the square planar geometry of the thiosemicarbazone copper(II) complexes 1–9. From the results of antibacterial activity against selected Gram-positive (Bacillus thuringiensis) and Gram-negative (Escherichia coli) bacterial strains, complex 8 exhibited noteworthy activity. Interestingly, copper(II) complexes bearing 1,10-phenanthroline (phen) moiety displayed outstanding results together with N(4)-substituted thiosemicarbazone derivatives and causes complete DNA degradation of SC (supercoiled) pUC18 DNA. Conclusion: A variety of substitutions at the thioamide nitrogen atoms have shown potential biological activity. Henceforth, N(4)-substituted thiosemicarbazone based copper(II) complexes virtually reach the effectiveness of conventional chemotherapeutic drugs.